BEYOND PROFIT AND PLAY: GAME-BASED SOCIAL ENTREPRENEURSHIP AS A CATALYST FOR SUSTAINABLE IMPACT - Ethan Tan; Ava Lee; Thomas Mitchell; Dodi Setiawan Riatmaja (Yayasan Adra Karima Hubbi, 2026)
The increasing complexity of global social and environmental challenges has intensified the need for innovative models of social entrepreneurship that move beyond conventional profit-oriented and philanthropic approaches. Game-based systems have emerged as interactive digital mechanisms capable of fostering sustained engagement, behavioral change, and collective action, yet their strategic role in social entrepreneurship remains underexplored. This study aims to examine how game-based social entrepreneurship functions as a catalyst for sustainable impact by integrating interactive design with social value creation. A qualitative multiple-case research design was employed, involving eight social enterprises that systematically utilize game-based mechanisms to address social and environmental challenges. Data were collected through semi-structured interviews, document analysis, and platform engagement metrics, and analyzed using thematic and comparative techniques. The results indicate that social enterprises embedding narrative-driven gameplay, cooperative mechanics, and mission-linked feedback systems achieve higher levels of sustained user engagement, mission alignment, and impact scalability. Game-based systems were found to operate as structural infrastructures rather than supplementary engagement tools. The study concludes that game-based social entrepreneurship represents a transformative model that bridges digital innovation and sustainability, enabling social enterprises to translate participatory play into durable social impact and long-term value creation.